2017
DOI: 10.1556/1886.2017.00008
|View full text |Cite
|
Sign up to set email alerts
|

Colonization with multidrug-resistant bacteria — on the efficiency of local decolonization procedures

Abstract: The effectiveness of a disinfectant-based decolonization strategy for multidrug-resistant bacteria like extended spectrum β-lactamase (ESBL)-positive Gram-negative bacteria with or without additional fluoroquinolon and carbapenem resistance as well as vancomycin-resistant enterococci and methicillin-resistant Staphylococcus aureus was assessed.Between 2011 and 2015, 25 patients from Libya, Syria, and the Ukraine with war traumata were treated at the Bundeswehr hospital Hamburg. The patients were heavily coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The hygiene management of injured patients is also complicated by colonization or infection with multidrug-resistant bacteria, although nosocomial transmission in military medical facilities can be widely prevented if strict hygiene precautions are enforced [ 54 , 55 ]. The effects of local skin or mucous membrane disinfection on decolonization of such sites are moderate in comparison to spontaneous decolonization rates and depend on the compliance of the patients [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hygiene management of injured patients is also complicated by colonization or infection with multidrug-resistant bacteria, although nosocomial transmission in military medical facilities can be widely prevented if strict hygiene precautions are enforced [ 54 , 55 ]. The effects of local skin or mucous membrane disinfection on decolonization of such sites are moderate in comparison to spontaneous decolonization rates and depend on the compliance of the patients [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of considerable efforts to achieve local decolonization by disinfectant washing, the results were only moderately better than the spontaneous decolonization rates. In addition, the effects depended on the compliance of the patients [ 56 ].…”
Section: Experience From Military Medical Healthcare Facilities Inmentioning
confidence: 99%
“…A significant decrease in colonization rate has been reported in association with the nasal wash using water twice daily 15 . This has been confirmed by a more recent study which found that patients' compliance with decolonizing washing procedures was associated with successful decolonization of multidrugresistant bacteria 16 .…”
Section: Introductionmentioning
confidence: 59%
“…Substance-specific genes and genes encoding efflux pumps mediating tolerance to disinfectants were observed in Enterobacterales. Therefore, further monitoring of the spread of disinfectant tolerance-associated genes and the effects of their abundance on disinfectant-based skin and wound decolonization strategies [ 36 ] seem advisable.…”
Section: Discussionmentioning
confidence: 99%